ﺗﺳرب طﻼب اﻟﻣدرﺳﺔ اﻻﺑﺗداﺋﯾﺔ ﻓﻲ ﺑﻐداد اﻻﺷﻛﺎﻟﯾﺎت واﻟﻔرص (Journal of the College of Education for Women, 2019)
Waste is the most common phenomenon in the educational systems. Such a waste should reduce its efficiency and weaken its productivity which is best represented by failing and dropouts .thus resources meant to develop the educational institutions quality and quantity–wise would be wasted .in other words the return of the investments allotted to develop the educational system would fall short of the aims . The consequences would worst in the primary learning field. The research has three chapters: The first chapter is about significance of the research and its aims in addition to a review of literature. The second chapter is about the concept of dropping out of schools in the primary learning sector plus a history of the phenomenon .Third chapter is a field survey conducted by the researcher in six schools in Baghdad .Teachers (male and female) were interviewed for their views on the problem of dropping out from primary schools.